A Young Lady with Quadriparesis (Journal of Medicine, 2023)
Neuromyelitis optica spectrum disorder (NMOSD) is a rare autoimmune disease, causing multifocal CNS inflammation affecting the optic nerves & spinal cord. In the 20th century, ‘Devics disease’ was considered as a variant of Multiple sclerosis(MS) that spared the brain. However, the discovery of IgG-class antibodies that bind to the water channel aquaporin-4 (AQP4-IgG) in serum from patients with Devic’s disease, but not from those with typical MS, established NMO as a distinct entity with a chronic, relapsing course. Our patient, a 42-year-old woman has been suffering from vomiting for 2 months followed by inability to move all extremities for last 7 days. It was the very 1st episode of such type of illness. We are reporting this case to highlight the presentation of NMOSD, which is itself a rare disease, outcropped as ‘Area postrema syndrome’, an inaugural manifestation in this patient.J MEDICINE 2023; 24(2): 158-161